Perencanaan Rencana Anggaran Biaya RumahTinggal dengan Pendekatan Inovatif di Kota Kendari - Nesya, Badzlina Harvy; Alvanda, Muhammad Reyhan; Habibulloh, Abdi; Nugroho, Shabrina Salsabila (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2025)
Kendari is the capital city of Southeast Sulawesi Province which administratively has 11 sub-districts and 65 villages. In 2023, the population of Kendari City reached 351,051 people which is increasing from year to year. This increase in population causes the need for houses as a basic need for housing for the community to also continue to increase from year to year. The house as a residence is certainly the key to the comfort and safety of its inhabitants. This comfort and security cannot be separated from efficient and effective house construction planning so that these goals can be achieved properly. The purpose of this research is to obtain detailed specifications of innovative implementation methods and materials that can make the construction of residential houses with a Budget Plan (RAB) that becomes effective and efficient and prioritizes aspects of quality and high quality. The data studied in this research is a residential house with an area of 7m x 9.5m located in Kendari City, Southeast Sulawesi Province. The results obtained are the calculation of the Cost Budget Plan (RAB) of Rp318,419,000 and the innovations applied to achieve the effectiveness and efficiency of residential construction, namely the calculation of the quantity of work items by prioritizing good waste management aspects, the use of high-quality products, casting using mini ready mix concrete with maintained quality, and innovative use of technology such as SketcUp 3D and Microsoft Project for efficient project execution and scheduling methods.